2015
DOI: 10.3390/nano5042212
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Morphological Tuning of LiCoPO4 Materials Synthesized by Solvo-Thermal Methods for Li-Cell Applications

Abstract: , in order to obtain higher redox potentials. In this communication we report a systematic analysis of the synthesis condition of LiCoPO4 (LCP) using a solvo-thermal route at low temperature, the latter being a valuable candidate to overcome the theoretical performances of LFP. In fact, LCP shows higher working potential (4.8 V vs. 3.6 V) compared to LFP and similar theoretical capacity (167 mAh·g −1 ). Our goal is to show the effect of the synthesis condition of the ability of LCP to reversibly cycle lithium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…62 Mixing an organic solvent and water as a co-solvent has been employed in the solvothermal synthesis of LiCoPO 4 . 44,45,[62][63][64] The solvent mixture can be benecial for effectively tailoring the particle size of LiCoPO 4 due to the high viscosity of the organic solvent, 62,63 and the water component can promote the dissolution of the reagents. 62 However, optimisation of solvothermal conditions to achieve LiCoPO 4 cathodes with good specic capacity and cycle performance is still challenging.…”
Section: Introductionmentioning
confidence: 99%
“…62 Mixing an organic solvent and water as a co-solvent has been employed in the solvothermal synthesis of LiCoPO 4 . 44,45,[62][63][64] The solvent mixture can be benecial for effectively tailoring the particle size of LiCoPO 4 due to the high viscosity of the organic solvent, 62,63 and the water component can promote the dissolution of the reagents. 62 However, optimisation of solvothermal conditions to achieve LiCoPO 4 cathodes with good specic capacity and cycle performance is still challenging.…”
Section: Introductionmentioning
confidence: 99%
“…All samples are single‐phase without any additional peaks except LiMg 0.2 Co 0.8 PO 4 , which contains some diffraction peaks from an impurity phase, assigned to Li 3 PO 4 (ICSD database no.77095). It has been reported that the formation of impurities depends on the concentration and pH of reagents in hydrothermal and solvothermal synthetic methods . In this study, additional MgSO 4 may influence the pH of reaction medium, resulting in the formation of impurity phase Li 3 PO 4 .…”
Section: Resultsmentioning
confidence: 77%
“…It has been reported that the formation of impurities depends on the concentration and pH of reagents in hydrothermal and solvothermal synthetic methods. [47,48] In this study, additional MgSO 4 may influence the pH of reaction medium, resulting in the formation of impurity phase Li 3 PO 4 .…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations